The Role of Constitutional Law in the Regulation of Higher Education in Indonesia: Between Academic Freedom and State Control - Rukmono, Indra; Soediono, Ricardo; Muttaqin, Labib; Ramadhan, Muh. Rivai (LP3M Universitas Islam Zainul Hasan Genggong, 2023)
This research aims to analyse the role of Constitutional Law (HTN) in regulating higher education in Indonesia, especially in maintaining the balance between academic freedom and state supervision. The method used in this research is the normative juridical method, which focuses on the study of legislation related to higher education as well as legal practices applied in Indonesia. The analysis is conducted on Law No. 12/2012 on Higher Education and Law No. 20/2003 on the National Education System, as well as other implementing regulations. The results show that HTN has two main roles in higher education in Indonesia. First, HTN acts as an instrument that regulates and supervises higher education institutions to ensure education remains in accordance with national goals and the basic principles of the state. Second, HTN also serves to protect academic freedom, which is a fundamental right guaranteed by the constitution. However, tensions often arise between the academic freedom that must be protected and state supervision aimed at maintaining the quality of education. In the discussion, it was found that while state supervision is essential to maintain the relevance and quality of higher education, overly restricted academic freedom can stifle innovation and creativity in education. Therefore, wise policies are needed to create a healthy balance between state oversight and academic freedom. Thus, higher education in Indonesia can serve as a means for the nation's progress without sacrificing the freedom of thought that is essential for the development of science.